Insolvency and debt recovery procedures in economic development: An overview of African law - Clas Wihlborg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Insolvency and debt recovery procedures are as crucial to a well-performing financial sector as credit provision itself. They are even more important in Africa, where attempts are underway to create fully-fledged financial markets. For the financial system to be credible, creditors must be ensured that lenders will meet their obligations and that cases against them will be brought to closure. A good legal framework for insolvency also ensures distressed firms a form of orderly exit, thereby enabling their owners to start afresh. However, institutions of this nature take time to take effect, and need to be supported politically and by reforms in other sectors of the economy.
Keywords: E6; G3; K0; K4; 330; legal reforms; credibility; bankruptcy; debt recovery; Insolvenzrecht; Afrika